2022
DOI: 10.1002/adsc.202200524
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Synthesis of β‐Hydroxy Amides (Esters) and γ‐Amino Alcohols via Ir/f‐Diaphos Catalyzed Asymmetric Hydrogenation

Abstract: The iridium/f‐diaphos L2 or L9 catalyzed asymmetric hydrogenation of β‐aryl β‐keto amides (esters), and β‐amino ketones to afford two enantiomers of the desired chiral alcohols was realized with 90%‐99% yield and 73%‐99% ee. This protocol could be easily conducted on gram scale in the presence of low catalyst loading (up to 9900 TON). Moreover, the hydrogenated products are versatile building blocks for a variety of biologically active molecules and drugs, such as Fluoxetine, Dapoxetine and so on.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In 2022, Zhong [66] et al reported the Ir/ f ‐diaphos catalyzed asymmetric hydrogenation of β‐aryl β‐keto amides 38 (Scheme 35), affording the corresponding chiral β‐hydroxy amides 39 with high yields (up to 99%) and excellent enantioselectivities (up to 99% ee) (Scheme 35). With the conformational shift of f ‐diaphos ligands, both ( R ) and ( S ) enantiomers of the desired chiral products could be obtained with similar activity.…”
Section: Asymmetric Hydrogenation Of C=o Bondsmentioning
confidence: 99%
“…In 2022, Zhong [66] et al reported the Ir/ f ‐diaphos catalyzed asymmetric hydrogenation of β‐aryl β‐keto amides 38 (Scheme 35), affording the corresponding chiral β‐hydroxy amides 39 with high yields (up to 99%) and excellent enantioselectivities (up to 99% ee) (Scheme 35). With the conformational shift of f ‐diaphos ligands, both ( R ) and ( S ) enantiomers of the desired chiral products could be obtained with similar activity.…”
Section: Asymmetric Hydrogenation Of C=o Bondsmentioning
confidence: 99%
“…Hu et al published an iridium catalyzed asymmetric hydrogenation of β - keto esters within chiral ferrocenyl P,N,N-ligands, providing good to excellent enantioselectivity. Zhong et al developed tridentate ferrocene-based diamine-phosphine sulfonamide ligands (f -diaphos) for the asymmetric hydrogenation of not only β-aryl-β-keto amides (esters) but also β-amino ketones to afford remarkably high enantioselectivity . Most recently, our group has synthesized cinchona-alkaloid-based NNP ligands, which perform well not only in iridium- and ruthenium-catalyzed carbonyl asymmetric hydrogenation systems but also in iridium-catalyzed asymmetric transfer hydrogenation systems .…”
Section: Introductionmentioning
confidence: 99%
“…However, the poor stability of catalysts and the insolubility of reactants in water or other shortcomings have hindered the utilization of water as a solvent. Following our continued pursuit of efficient, green and safe methodologies for the construction of chiral molecules, 24,25 herein we present a manganese-catalyzed asymmetric transfer hydrogenation of quinolines in water. This innovative approach employs readily available chiral aminobenzimidazole ligands, resulting in the desired chiral 1,2,3,4-tetrahydroquinolines with up to 99% ee and 97% yield (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%